INTERAÇÕES ENTRE POPULAÇÕES TRADICIONAIS COM ESPÉCIES DE RÉPTEIS E MAMÍFEROS DO PARQUE NACIONAL DOS LENÇÓIS MARANHENSES - SANTOS, Pedro Victor Cardoso dos (2024)
Traditional knowledge is transmitted over generations, the result of diverse interactions between people and the environment. Such knowledge is susceptible to the influence of several factors, such as: age, income, education, location and culture, which directly interfere with the acquisition of this knowledge within human communities. Other factors, such as emotional factors, associated with perceptions about fauna, can influence positive or negative attitudes, depending on the species and aesthetic attributes. Thus, the current study aims to investigate how the effects of human perceptions can enhance the preservation or persecution of species of reptiles and mammals, in addition to comparing perceptions about fauna in different traditional communities in the Lençóis Maranhenses National Park. Data collection took place through semi-structured questionnaires and free conversations, where each participant provided information about interactions with fauna, perceptions and attitudes. From the data analyzed, we found that the locality variable has a significant influence on traditional faunal knowledge. Additionally, negative values (anger, disgust and danger) tend to generate negative attitudes towards wild animals. While positive values (importance of the animal, liking the animal and usefulness) promote positive attitudes. The complexity of these interactions must be considered when developing conservation strategies and management.